Methodologies in Spinoza and Aristotle: a comparative analysis - Corazza, Michael, author; Romagni, Domenica, advisor; Harris, Eirik, committee member; Margolf, Diane, committee member (Colorado State University. Libraries, 2025)
For this project, I aim to identify a shared methodological structure in Spinoza's and Aristotle's accounts of human flourishing—particularly as developed in the Ethics and the Nicomachean Ethics. This structure consists of a progression that begins with the definition of a thing, proceeds to its natural activity, and culminates in an account of that activity's highest expression. In Chapter 1, I review the philosophical positions of Spinoza and Aristotle that are relevant to this analysis. In Chapter 2, I consider Spinoza's theories of essence, striving, and blessedness alongside Aristotle's theories of form, function and sophia, concluding that the similarities between these principles are limited. Finally, in Chapter 3, I analyze how the principles discussed in Chapter 2 ground separate accounts of the good life. I argue that despite their differences, these principles function in a parallel way methodologically, with each successive idea explanatorily reliant on its predecessor.
Keywords: flourishing; philosophical methodology; Aristotle; Spinoza; history of philosophy